Upaya Meningkatkan Konsentrasi Belajar Peserta Didik Dengan Bantuan Ice Breaking Pada Kelas V SDN 16 Mataram Tahun Ajaran 2022/2023 - Ningrum, Ketut Puspita; Mahardikha, Deni Tri Agus; Istiningsih, Siti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
The purpose of this study is to increase the concentration of students' learning through icebreaking activities in class V SDN 16 Mataram in the academic year 2022/2023. This type of inquiry is a collaborative classroom inquiry. The data collection methods used in this study were observation, questionnaire and documentation. The study involved 21 subjects namely students of class V SDN 16 Mataram. The results of the study show that there is an increase in the concentration of student learning, and then in student learning outcomes, as can be seen from the pre-course results: 52% in the poor category (K), then in the 1st cycle there was an increase to 65% in the “good” category (B) and in cycle 2 increased to 81% in the “very good” (SB) category.